Benefits of Applying E-Commerce in Companies of Vietnam - Nguyen Tan , Danh (International Journal of Psychosocial Rehabilitation, 2020)
The scientific and technological revolution has been bringing about dramatic changes throughout the world. The application of information technology in economic activities brings tremendous benefits to the whole society. E-commerce is a field of economic activity that is no stranger to many countries. People no longer have to spend time, effort and money on economic transactions. The application of 5G technology in business activities is an indispensable trend, and Vietnam - in the integration process is not outside the development trend. The process of developing e-commerce in Vietnam still faces many difficulties and requires objective studies on the law of e- commerce advocacy and development from which to build and deploy strategies for developing this field of commercial activity. The paper focuses on analyzing the importance of e-commerce and its application in national economic development in order to improve competitiveness in terms of integration.